Recent advances in single crystal diamond device fabrication for photonics, sensing and nanomechanics - Rani, Dipti; Opaluch, Oliver Roman; Neu, Elke (Micromachines, 2021)
In the last two decades, the use of diamond as a material for applications in nanophotonics, optomechanics, quantum information, and sensors tremendously increased due to its outstanding mechanical properties, wide optical transparency, and biocompatibility. This has been possible owing to advances in methods for growth of high-quality single crystal diamond (SCD), nanofabrication methods and controlled incorporation of optically active point defects (e.g., nitrogen vacancy centers) in SCD. This paper reviews the recent advances in SCD nano-structuring methods for realization of micro-and nano-structures. Novel fabrication methods are discussed and the different nanostructures realized for a wide range of applications are summarized. Moreover, the methods for color center incorporation in SCD and surface treatment methods to enhance their properties are described. Challenges in the upscaling of SCD nano-structure fabrication, their commercial applications and future prospects are discussed.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Diamond; Nanofabrication; Photonics; Quantum technologies